ALKBH5 gene polymorphisms and Wilms tumor risk in Chinese children: A five‐center case‐control study. Issue 6 (24th February 2020) - Hua, Rui‐Xi; Liu, Jiabin; Fu, Wen; Zhu, Jinhong; Zhang, Jiao; Cheng, Jiwen; Li, Suhong; Zhou, Haixia; Xia, Huimin; He, Jing; Zhuo, Zhenjian
Abstract: Background: Wilms tumor is a frequently diagnosed renal cancer among children with unclear genetic causes. N6‐methyladenosine (m 6 A) modification genes play critical roles in tumorigenesis. However, whether genetic variations of m 6 A modification genes predispose to Wilms tumor remain unclear. ALKBH5 (AlkB homolog 5), a crucial member of m 6 A modification genes, encodes a demethylase that functions to reverse m 6 A RNA methylation. Methods: Herein, we evaluated the association of single nucleotide polymorphisms (SNPs) in the m 6 A modification gene ALKBH5 and Wilms tumor susceptibility in a large multi‐center case‐control study. A total of 414 Wilms tumor cases and 1199 healthy controls were genotyped for ALKBH5 rs1378602 and rs8400 polymorphisms by TaqMan. Results: No significant association was detected between these two polymorphisms and Wilms tumor risk. Moreover, 1, 2, and 1‐2 protective genotypes (rs1378602 AG/AA or rs8400 GG) did not significantly reduce Wilms tumor risk, compared with risk genotypes only. Stratification analysis revealed a significant relationship between rs1378602 AG/AA genotypes and decreased Wilms tumor risk in children in clinical stage I diseases [adjusted odds ratio (OR) = 0.56, 95% confidence interval (CI) = 0.32‐0.98, P  = .042]. The presence of 1‐2 protective genotypes was correlated with decreased Wilms tumor risk in subgroups of age > 18 months, when compared to the absence of protective genotypes (adjusted OR = 0.74, 95% CI = 0.56‐0.98, P  = .035). Conclusion: Collectively, our results demonstrate that ALKBH5 SNPs may exert a weak influence on susceptibility to Wilms tumor. This finding increases the understanding of the role of the m 6 A gene in tumorigenesis of Wilms tumor.